Conflitos recentes, estruturas persistentes: notícias do Sudão - Perrone-Moisés, Beatriz (Revista de Antropologia, 2001)
In March 2000, a Dinka-Nuer peace treaty was signed in southern Sudan. The civil war that had been going on for decades, as well as the resolutions adopted, described in the press and present in the documents, acquire full meaning when one considers Evans-Pritchard's deep analysis of Nuer politics. The nuer structures revealed in his works, having persisted for decades, pass the "test of history", and lead to a reconsideration of his contributions to the understanding of the inter-play between structure and history